In BOLD we trust? A commentary on the reliability of specimen identification for DNA barcoding: a case study on burrower bugs (Hemiptera: Heteroptera: Cydnidae) - Lis, Jerzy A.; Lis, Barbara; Ziaja, Dariusz J. (Zootaxa, 2016)
An assessment was performed regarding the accuracy of various types of data deposited in the Barcode of Life Data system (BOLD) related to the true bug family Cydnidae (Hemiptera: Heteroptera). Taxonomic nomenclature and classification, identification reliability, and the correctness of the data provided in the “Taxon description” were analyzed and commented on with respect to both available versions of the BOLD system, i.e. version 3 and beta version 4. Numerous mistakes in taxonomy, the relevance of the taxa names, and species misidentifications in BOLD version 3 were found and, more importantly, similar errors were detected in BOLD version 4 as well. We suggest that if the BOLD system is presumed to be taxonomically trustworthy, it can’t exist without an adequate a priori identification of barcoded specimens. Otherwise, the erroneous data deposited onto the BOLD platform will have a negative impact on studies in which molecular data imported from BOLD are utilized.